Jigsaw puzzle to teach anatomy to first year MBBS students - Gupta, Seema; Soni, Anshu; Singh, Sonia; Vohra, Hitant (International Journal of Research in Medical Sciences, 2019)
Background: Anatomy provides a platform of knowledge indispensable to all the branches of medicine. Students have to learn many new concepts and tongue-twisting terminologies, making this subject difficult to comprehend. It has been seen that a range of innovative, proactive, simple, hands-on approach strategies can achieve maximum student engagement and help them learn. Aim is to take students from the traditional view of anatomy as a subject that require surface learning (rote learning, memorization) to one that can lead to deep learning through understanding. Keeping all this in mind a study was planned to develop an innovative method of teaching anatomy to 1st year MBBS students. Methods: The diagrams of sagittal and horizontal sections of the brain were selected, marked and cut into jigsaw pieces. Students were given an incomplete jigsaw puzzle and a set of questions. The answer to these questions helped them complete the puzzle. Perception of students who consented to participate in the study was noted. Results: Out of 98 students who participated in the study 61.2% wanted to participate in similar activities in future in anatomy and 57.1% felt that it helped them in understanding the topic. For 52.1% it was a useful self-learning tool and for another 48.9% students solving the puzzle was a challenging experience. Conclusions: Jigsaw puzzle is an efficient way for students to become engaged in their learning. It maximizes interaction and establishes an atmosphere of co-operation and respect for other students and improves learning.